2018
DOI: 10.1038/s41598-017-18710-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of short acute UVB treatments in Chenopodium quinoa Willd

Abstract: Increased ultraviolet B (UVB) radiation due to global change can affect plant growth and metabolism. Here, we evaluated the capacity of quinoa to resist under short acute UVB irradiation. Quinoa was daily exposed for 30 or 60 min to 1.69 W m−2 UVB. The results showed that 30 min exposure in 9 d-course did not cause severe alterations on photosynthetic pigments and flavonoids, but a significant increase of antioxidant capacity was observed. Otherwise, 60 min UVB in 5 d-course reduced almost all these parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Recently, Reyes et al (2018) reported the first study on the effect of UV-B on quinoa photosynthesis [238]. In this study, chlorophyll fluorescence, pigment synthesis, photosynthesis, and ROS accumulation were affected by different levels and duration of UV-B.…”
Section: Ultraviolet B (Uv-b) Radiationmentioning
confidence: 61%
“…Recently, Reyes et al (2018) reported the first study on the effect of UV-B on quinoa photosynthesis [238]. In this study, chlorophyll fluorescence, pigment synthesis, photosynthesis, and ROS accumulation were affected by different levels and duration of UV-B.…”
Section: Ultraviolet B (Uv-b) Radiationmentioning
confidence: 61%
“…In addition, the unbalanced visible radiation/UV-B is an experimental strategy commonly used (i.e. [11, 35, 39]) to magnify the effect of a single stress in plants, which can be useful for elucidation of response mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites, like flavonoids, have special roles in determining plants quality because they contribute to the colours and flavours of vegetables and fruits, and may have high antioxidant levels that help protect humans from degenerative diseases 13 . Fertilization can increase biomass production in medicinal plant, vegetable and crop cultivation systems; however, it can decrease the biosynthesis and accumulation of physiologically active substances, including flavonoids and terpenes, and further impact the quality of raw materials 4,5 .…”
Section: Introductionmentioning
confidence: 99%